Changes in white blood pictures and some biochemical parameters of dairy cows in peripartum period and early lactation - Mirjana Joksimović Todorović; Vesna Davidović (Mljekarstvo)
The objective of this research was to determine the changes in the number of cells of white blood line and some biochemical parameters: concentration of glucose, concentration of non-esterified fatty acids (NEFA), activity of enzymes of aspartat aminotransferase (AST), alanin aminotransferase (ALT) and gamma glutamyltranferase (GGT), in 17 Holstein-Friesian breed dairy cows in peripartum period and early lactation (on d 15 prepartum, on the day of parturition and on d 15, 30, and 45 postpartum). The highest values of total leukocytes count, neutrophiles, monocytes and basophiles count were recorded on the day of parturition, and then decreased, so that the minimum value established on d 45 of lactation. The lymphocytes count was the lowest on the day of parturation, while the eosinophils and basophiles counts were significantly different in observed time intervals. The concentration of glucose ranged from 3.07 mmol/L on d 15 prepartum to 2.71 mmol/L on d 15 postpartum. A high concentration of non-esterified fatty acids (NEFA) in the postpartum period is a consequence of changes in energy balance and more intensive process of lypolisis in fat tissue, due to energy disbalance at the beginning of lactation. Established activity of enzymes AST, ALT and GGT was approximately the same in studied time intervals and was within physiological limits. The results of hematological and biochemical analysis in this paper do not indicate the development of postpartum ailments, because the investigated parameters were within physiological limits.